HUBUNGAN PENGETAHUAN DENGAN PENERAPAN ERGONOMI TUBUH SAAT PEMBELAJARAN ONLINE PADA MAHASISWA TINGKAT II PRODI NERS STIKES SANTA ELISABETH MEDAN TAHUN 2022 - Samfriati Sinurat; Friska Ginting; Diana Abigail Siagian (Bajang Institute, 2023)
Ergonomics while studying is an effort to make the study room a comfortable place to study so that one inner energy can be used for learning activities only and does not go to waste because they have to face a non-ergonomic environment. If the posture while studying is not ergonomic, a person will easily get tired, and abnormalities in the bones and muscles can occur. Learning behavior during online learning using a computer or laptop is related to ergonomics. Knowledge of good ergonomics will change the behavior of sitting in front of a laptop or computer. This study aims to determine the relationship between knowledge and the implementation of body ergonomics during online learning in second year nursing students at STIKes Santa Elisabeth Medan 2022. The research design type used is cross-sectional with a total sampling of 93 respondents. The study results obtain good knowledge (72%) and good ergonomics application (48.4%). The results of the chi-square test obtain p-value = 0.109 (p>0.05). This study results show no relationship between knowledge and the implementation of body ergonomics during online learning in second year nursing students of the STIKes Santa Elisabeth Medan 2022. It is recommended for respondents to maintain a good ergonomic position and increase self-awareness in doing a good ergonomic position during online learning.